Socialization of Modern Futsal Refereeing Practices for FIKK Students of UNM Makassar - Muh. Syaiful Syam; Benny Badaru; Andi Ridwan; M. Said Zainuddin; Suwardi Suwardi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pejuang Republik Indonesia, 2026)
This Community Service Program (PKM) aimed to improve the knowledge, understanding, and skills of students of the Faculty of Sports Science and Health (FIKK), Universitas Negeri Makassar, in modern futsal refereeing practices. The rapid development of futsal requires the improvement of human resource competencies, particularly in refereeing that aligns with the latest regulations and modern match standards. The implementation method of this activity was carried out through socialization, material presentation, practical demonstrations, match simulations, and evaluation of participants’ understanding. The participants consisted of FIKK UNM Makassar students who had an interest in futsal and sports refereeing. The results of the activity showed an improvement in students’ understanding of the latest futsal game rules, referee decision-making techniques, communication during matches, referee positioning, as well as the use of technology and modern match mechanisms. This activity had a positive impact on improving students’ competencies in futsal refereeing and is expected to support the development of futsal both within the university environment and the wider community.